Designing the Teenpreneur Interactive Digital Module to Support Entrepreneurial Interests and Soft Skills Development in High Schools in Gresik City - Tyas Nastiti; Alfina Alfina; Marisya Khoirina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In fact, entrepreneurial learning is not solely to produce a product and to seek business benefits as much as possible. In learning entrepreneurship learners are not only required to create a product and market it. However, learners are given a positive understanding of an entrepreneurial activity that is an entrepreneur who has many creative ideas, and is innovative, not afraid of a new challenge and able to face risks. In conducting this research, researchers used descriptive qualitative research methods. In the process of collecting data researchers use observation methods, interviews and documentation. In conducting observations in the field, researchers act as observers. For the analysis, the author uses qualitative descriptive analysis techniques, namely written or oral data from the source and observed behavior so that in this case the author describes the whole thing about the actual situation. The products produced from this research are expected not only to develop entrepreneurial abilities, but also to develop basic skills of negotiating, communicating, and creativity or often called soft skills.